KONSEP PENALARAN BAYANI, BURHANI DAN INFARNI - Razali, Razali (Proceeding International Seminar of Islamic Studies, 2024)
This paper seeks to elucidate the concepts of bayani, irfani and burhani reasoning in the teaching of Aqidah Akhlak within the framework of Islamic education. Innovations in Aqidah Akhlak education in Islamic schools aim to address the developmental challenges faced by children. The orientation and goal of Islamic education involves establishing early integrity and national loyalty among students. Therefore, there is a need to intensify efforts in the field of knowledge. Key areas that require attention include: first, updating the epistemological approach based on the history of Islamic civilization and adapting the curriculum accordingly. Second, reforming the epistemological paradigm of Bayani reasoning to include Abid al-Jabiri's trilogy of reasoning Bayani reasoning, Irfani reasoning, and Burhani reasoning in Aqidah Akhlak's instruction. Although these three forms of reasoning are interconnected, Bayani reasoning is accorded top priority, fostering a mutually reinforcing relationship between them. Third, the alignment of the curriculum with global issues relevant to Aqidah Akhlak learning materials, reflecting contemporary era progress and the complex challenges facing humanity, especially the Muslim community. Addressing these issues requires local and global actions, responding to the de-escalation.